Aqueous Cr(VI) removal by a novel ball milled Fe0-biochar composite: Role of biochar electron transfer capacity under high pyrolysis temperature. (February 2020) - Wang, Kun; Sun, Yuebing; Tang, Jingchun; He, Juan; Sun, Hongwen
Abstract: A novel ball milled Fe 0 -biochar composite was synthesized by ball milling the mixture of biochar (pyrolyzed at 300 °C, 500 °C, and 700 °C) and micron grade iron powder. FTIR, SEM, TEM-EDS, XRD, and XPS were applied to characterize this composite. XRD results showed that iron carbide phase was formed during the ball milling process. The ability of this synthesized composited to remove aqueous Cr(VI) was tested. Removal rates of Cr(VI) (49.6%, 65.8%, and 97.8%, respectively) by ball milled Fe 0 -biochar composite consisting of biochar pyrolyzed at 300 °C (300BMFe 0 -BC), 500 °C (500BMFe 0 -BC), and 700 °C (700BMFe 0 -BC) were much higher than those (19%, 11%, and 4%, respectively) by pristine biochar pyrolyzed at 300 °C (300BC), 500 °C (500BC), and 700 °C (700BC). Cr(VI) removal rate by 700BMFe 0 -BC increased from 15.4% to 97.8% when prolonging ball milling time from 6 h to 48 h. Ball milling promoted the combination of Fe 0 and biochar as well as reduced the hydrodynamic diameter of the composite. Acidic conditions favored Cr(VI) removal. Ball milling exposed the functional groups of biochar and improved its Cr(VI) removal rate. Raman spectra showed that the degree of graphitization in 700 °C ball milled biochar (700BMBC) was the highest. Electrochemical analysis demonstrated that 700BMBC had the highest electron transfer capacity. In the presence of Fe 0, graphitized structure in 700BMBC acted as an electron conductor, facilitating electron transfer from Fe 0 to Cr(VI). Ball milling also destroyed the surface iron oxide layer to regenerate the composite. Graphical abstract: Image 1 Highlights: Ball milled Fe 0 -biochar composite was successfully synthesized by ball milling for the first time. Ball milled Fe 0 -biochar composite consisting of biochar pyrolyzed at 700 °C had the highest Cr(VI) removal rate of 97.8%. Ball milling exposed the functional groups of biochar and promoted Cr(VI) removal. Graphitized structure in 700BMBC acted as an electron conductor and facilitated electron transfer from Fe 0 to Cr(VI).